POLA KOMUNIKASI HUMAS SEKRETARIAT DPRD DALAM MENYAMPAIKAN INFORMASI KEPADA MASYARAKAT KABUPATEN KATINGAN: Pattern Of Communication Of Private Regency Of DPRD Secretariat In Delivering Information To The Community Of Katingan Regency - Rahman, Sirojul; Laduni, Alif Fajar (Pencerah Publik, 2022)
This study aims to find out how the PR Communication Patterns of the DPRD Secretariat in Delivering Information to the Katingan Regency Community, because the DPRD is an organizing element of the regional government in filtering aspirations and conveying information. The method used in this research is descriptive qualitative where the technique of collecting data is by observing interviews and documentation. Data analysis used qualitative data analysis procedures, namely extracting meanings, describing explanations and determining the context of each data. The results showed that in this study the Public Relations Communication Patterns of the DPRD Secretariat in Delivering Information to the Community of Katingan Regency with the dissemination to the community carried out by the Public Relations of the DPRD Secretariat of Katingan Regency had a very large influence on creating a positive image in society. The role of Public Relations in the growth and development of the stability of the Katingan Regency DPRD as an element of local government administration and in achieving agency goals is very large. The dissemination of information is carried out in a planned and structured manner in programs that use the principles of public relations in their implementation. Barriers to the communication patterns of the Katingan Regency DPRD Secretariat lack of coordination between the Leaders and members of the Katingan Regency DPRD.